factors affecting of plate waste consumed by inpatients in permata bunda hospital malang - Melinda - Rimporok (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2019)
Plate waste is the amount of food which is left and not consumed by the inpatients and is disposed of as a waste, and also it can be used to measure the menu effectiveness. If there’s much plate waste in a long period of time, it will affect the patients’ nutrition status and could cause malnutrition. The imminent impacts are the prolonged patients’ recovery time, as well as the prolonged duration of the medical treatment, and also the increment of the inpatient cost. Factors affecting plate waste are internal factors and external factors of the inpatient room. Objective : To determine the regression of the food quality on the plate waste, the improper meal schedule, the matrons’ attitude towards the patients, the unsupportive medical environment, the food from the outside of the hospital, and the patients’ psychological condition. Method : Descriptive study along with observation. Research was done in the in-patients wards in Permata Bunda Hospital in Jln. Soekarno Hatta No. 75, Malang. There were 30 in-patients as the sample. Discussion : The percentage of the inpatients who didn’t consume their whole food is 39,44%. The patients’ psychological condition is 90% normal, no depression or anxiety. Meal schedule, 90% was on schedule with the same intake. Nutrition officers’ attitude, 90% gave sufficient information and treat the inpatients patiently. The medical treatment rooms, 16% patients didn’t feel relax and calm, 90% of the inpatients’ rooms were clean. 62% food is from outside hospital, in which 23% of the patients didn’t get used to the food from the hospital, 0,6% felt that the food from hospital wasn’t delicious, 39,5% thought that the food didn’t arouse the appetite, 2,2% felt that the food was tasteless and didn’t taste good. Conclusion : The food quality and taste have to be improved in order to accomodate the patients’ satisfaction. Monitoring and evaluation for plate waste is carried out periodically. Key words : Plate Waste, Patients, Hospital.